FAULTS AND GROUND UPLIFT AT ACTIVE CALDERAS - Folch A.; Gottsmann J. (My University, 2006)
Subsurface volume and pressure increases triggering surface inflation at active calderas are generally deduced by inverting ground-deformation time-series using isotropic and homogeneous half-space models (IHM). These models represent simplified mathematical analogues of the mechanical behaviour of the Earth's crust. Using three-dimensional numerical modelling, we show that lateral discontinuities such as intracaldera- or caldera-ring-faults can significantly amplify and distort the ground deformation pattern during unrest. As a consequence, data inversions using IHMs, which do not consider lateral discontinuities, can provide erroneous results on causative source parameters. We also find that the degree of amplification and distortion in the form of abrupt changes in displacement/distance gradients in proximity to faults is dependent on source geometry. Prolate bodies represent a particularly critical geometry for which pressure increases may be overestimated by a factor of up to three. Our 3D analysis suggests that amplification effects can be much larger than predicted by earlier 2D models. We validate theoretical results by applying our model to investigate the effect of boundary faults and source geometries on the displacement field during ground uplift at the restless calderas of Campi Flegrei (Italy) and Sierra Negra (Galapagos Islands, Ecuador). Based on the discrepancy in results from IHMs and our numerical model, we argue that employing IHMs for inversion of ground displacement and gravity time-series may in some cases lead to a biased assessment of hazards associated with ground uplift. © The Geological Society of London.